MODEL STRATEGI INTEGRATED MARKETING COMMUNICATION (IMC) KEDAI DIGITAL #10 SOLO DALAM MENGHADAPI PERSAINGAN USAHA DI BIDANG DIGITAL PRINTING - Anggraeni, Melinda Putri (JURNAL KOMUNITAS, 2013)
Business in digital printing is very competitive. This research aims to describe how digital printing company, especially Kedai Digital #10 able to survive in the competitive of digital printing industry. This field also aims to formulate a strategy based on the models of Integrated Marketing Communication (IMC) by Dwi Sapta and Tom Duncan. Using qualitatif descriptive, the data is obtained from observation, interviews, and documentation. Sampling techniques used purposive sampling. Techniques of data analysis is done by examining the data, data reduction, and heck out the presentation of the validity of the data. To ensure the validity of data done by triangulation technique. Result shows that the mix formulation of IMC strategy model by Dwi Sapta and Tom Duncan is more effective and efficient way to Kedai Digital # 10 Solo than just using one of strategy.